Food consumption markers and sociodemographic factors associated with obesity among adult women registered in the Food and Nutrition Monitoring System (SISVAN) in Brazil: a cohort study, 2015–2019 - Barros, Anael Queirós Silva; Aguiar, Italo Wesley Oliveira; Adriano, Lia Silveira; Carioca, Antônio Augusto Ferreira; Marchioni, Dirce Maria Lobo; Sampaio, Helena Alves de Carvalho (Frontiers in Public Health, 2024)
Introduction Carrying out studies using data from Food and Nutritional Monitoring is crucial given the current epidemiological scenario. This scenario reveals a coexistence of malnutrition and nutritional deficiencies alongside overweight and obesity, particularly among adult women in Brazil. Analyzing the microdata generated by the system is essential for accurately representing food and nutrition indicators in the country. Objective To analyze the association of food consumption markers and sociodemographic factors with changes in the Body Mass Index (BMI) among adult women. Methodology A cohort study with a final sample of 30,354 women evaluated through individual records between the years 2015 and 2019. Nutritional status was assessed using body mass index (BMI). Food consumption markers used were the ones available in the system, which referred to foods consumed the previous day. Linear regression was used to evaluate factors associated with BMI and multiple Poisson regression was used to estimate the relative risk of obesity incidence. Results There was an increase in BMI between 2015 and 2019. The average increase in BMI was lower in women who consumed, in the previous day, beans (β = −0,25; CI95%: −0.36; −0.13) and vegetables and/or legumes (β = −0.12; CI95%: −0.21; −0.04) and the increase was greater when they consumed hamburgers and/or sausages (β = 0.1; CI95%: 0.02; 0.19) adjusted by age, region and skin color. There was a 14% lower incidence of obesity in the group that consumed beans (RR = 0.86; 95% CI: 0.79; 0.93), and a 9% lower incidence when they consumed filled cookies, candies or treats (RR = 0.91; 95% CI 0.86; 0.96). The incidence of obesity was 11% higher in the group that consumed sweetened drinks (RR = 1.11; 95% CI: 1.05; 1.18) and 9% higher in the group that consumed instant noodles, packaged snacks or savory biscuits on the day before the 2015 registration (RR = 1.09; 95% CI: 1.03; 1.15). Conclusion There was an increase in BMI in the population of adult women, rising nationally between 2015 and 2019, with the notable influence of diet on this change.